2013
DOI: 10.1590/s1983-14472013000400012
|View full text |Cite
|
Sign up to set email alerts
|

Óbito neonatal precoce e tardio: perfil das mães e dos recém-nascidos

Abstract: The aim of the study was to analyze the profile of mothers and newborns who died in the early and late neonatal period. Descriptive, exploratory cross-sectional study that used secondary data obtained from the information systems of mortality, births and hospital records of mothers living in Cuiabá, who gave birth in 2010. We studied 77 deaths, of which 72.7% occurred in the early neonatal period. The early and late neonatal mortality rates were, respectively, 8.2, 6,0 and 2,2/1,000 live births. No difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
21

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 8 publications
1
3
0
21
Order By: Relevance
“…When birth is anticipated, NBs are exposed to risks, either because of their physiological immaturity or because they are already suffering from intrauterine distress. 23 A study carried out in Cuiabá/MT found that among neonatal deaths, the causes that were highlighted were less than seven prenatal consultations, prematurity and low birth weight. 24 In preterm births, the NB sometimes needs immediate care in the delivery room before being referred to the NICU, and physical skin-to-skin contact with the mother is delayed due to the child's conditions and institutional routines.…”
Section: Discussionmentioning
confidence: 99%
“…When birth is anticipated, NBs are exposed to risks, either because of their physiological immaturity or because they are already suffering from intrauterine distress. 23 A study carried out in Cuiabá/MT found that among neonatal deaths, the causes that were highlighted were less than seven prenatal consultations, prematurity and low birth weight. 24 In preterm births, the NB sometimes needs immediate care in the delivery room before being referred to the NICU, and physical skin-to-skin contact with the mother is delayed due to the child's conditions and institutional routines.…”
Section: Discussionmentioning
confidence: 99%
“…A via de nascimento predominante em Porto Velho correspondeu a cesariana (54,84%), cujos achados se equivalem aos estudos em que 56,7% (6) e 52% (18) dos óbitos neonatais foram de mães submetidas à cesárea.…”
Section: Discussionunclassified
“…Verificou-se que houve menor percentual de óbitos com o parto vaginal (42,29%), que contribui com o fortalecimento do sistema imunológico, o desenvolvimento do ritmo cardíaco e maturação pulmonar do RN. O parto vaginal é fisiológico e o corpo da mulher foi preparado para tal evento (18) . Além disso, um estudo realizado no Rio Grande do Sul relaciona a prematuridade como causa de parto cesáreo pela margem de erro na idade gestacional (19) .…”
Section: Discussionunclassified
“…Entretanto, morreram mais do sexo masculino (61,0%) e sobressaiu elevado percentual de prematuridade (75,3%) e baixo peso (72,7%), além de recém-nascidos com Apgar< 7 no 1° minuto, principalmente, entre aqueles que foram a óbito no período neonatal precoce. 15 Resultados estes também encontrados em outra pesquisa sobre mortalidade, que encontrou um maior predomínio de óbitos no sexo masculino (51,41%). 14 No que diz respeito às principais causas de óbitos, as causas perinatais, sem especificação, corresponderam a 19,61% dos casos totais.…”
Section: Quadro 1 -unclassified